THE INFLUENCE OF 4PS AS MARKETING STRATEGY ON PURCHASE INTENTION IN TRANSMART KAWANUA MANADO - Abas, Dewita Lucyana; Worang, Frederik G.; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
After facing the COVID-19 crisis, the retail industry needs to continuously innovate with effective marketing strategies to revive consumer purchase intentions. This study aims to identify the impact of the 4Ps aspects on customer purchase intentions at Transmart Kawanua Manado. Through the analysis of marketing strategies based on Product (X1), Price (X2), Place (X3), And Promotion (X4) as independent variables, with Purchase Intention (Y) as the dependent variable, a quantitative research method was used by collecting primary data from 100 respondents who are customers of Transmart Kawanua. The results show that while the products offered are standard and can be found in other shopping centers, location is not the main determining factor. However, effective pricing strategies and promotions play a significant role in attracting purchase interest. Additionally, all 4Ps aspects simultaneously influence customer purchase intentions at Transmart Kawanua. Therefore, an integrated marketing approach that considers all 4Ps aspects is crucial in enhancing customer engagement and business growth for Transmart Kawanua.    Keyword:s Marketing Strategy, Marketing Mix, Product, Price, Place, Promotion, Purchase Intention